2020
DOI: 10.3390/diagnostics10100814
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Applications of Iodine Quantification Using Dual-Energy CT: A Systematic Review

Abstract: Dual-energy computed tomography (DECT) can estimate tissue vascularity and perfusion via iodine quantification. The aim of this systematic review was to outline current and emerging clinical applications of iodine quantification within the gastrointestinal tract using DECT. The search was conducted with three databases: EMBASE, Pubmed and The Cochrane Library. This identified 449 studies after duplicate removal. From a total of 570 selected studies, 30 studies were enrolled for the systematic review. The studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 78 publications
(125 reference statements)
0
11
0
Order By: Relevance
“…More importantly, our study demonstrated iodine-uptake derived radiomics provided more powerful value to predict PM than the conventional one. DECT is a candidate modality to apply in the gastric tumor due to its insight into materials decomposition (29). Our previous researches have introduced the role of DECT combined with PET/CT in dynamically monitoring the process of peritoneal metastasis for GC in vitro (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, our study demonstrated iodine-uptake derived radiomics provided more powerful value to predict PM than the conventional one. DECT is a candidate modality to apply in the gastric tumor due to its insight into materials decomposition (29). Our previous researches have introduced the role of DECT combined with PET/CT in dynamically monitoring the process of peritoneal metastasis for GC in vitro (35).…”
Section: Discussionmentioning
confidence: 99%
“…For iodine concentration images, iodine quantitation was standardized in an in-house software (iodine standardization, Syngo via). The purpose of iodine standardization was to reduce the influence of technical or physiological differences resulting from variational cardiac output and phase time when loading iodine within tissues (29). A circular ROI inside the abdominal aorta was independently outlined for individuals on the portalvenous phase and delayed phase from the IU images, omitting calcified plaque secondary to atherosclerosis.…”
Section: Standardization For Iodine Concentrationmentioning
confidence: 99%
“…Moreover, the IC value of the non-response group was significantly lower than that of the response group, which may indicate that the relatively low blood supply of the tumor before chemotherapy has some difficulties in the targeted organ transportation of chemotherapy drugs, leading to a lower sensitivity of chemotherapy than that of the tumor with relatively rich blood supply before chemotherapy. Although NIC has been proven to be a relatively stable indicators in tumor staging and detection of HER2 status (53,54), its application and benefits are not entirely clear (55). Previous study revealed that NIC cannot serve as an independent predictive factor for lymph node metastasis in GC (51).…”
Section: Evaluation Of Clinical-radiomics Nomogram Performancementioning
confidence: 99%
“…As opposed to conventional CT where only a single energy level is used for imaging, Dual Energy CT (DECT) uses the attenuation measurements acquired at different energy spectra to differentiate and quantify material composition with the use of known changes in attenuation between the two spectra. In DECT, iodine can be separated and, with reconstruction algorithms, quantified as the iodine concentration, which may be used for assessment of tissue perfusion, tumor differentiation, and treatment response [ 9 ].…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%
“…In this special edition both case series, original research, and reviews are presented. The topics cover various vascular geometries using ultrasound, CT, MRI, and angiography [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%